Education in dispute in contemporary Brazil: among gender studies, the so-called gender ideology and the production of a 'genesis ideology' - Acosta, Tássio (2020)
This article is based on a reflexive-philosophical process about the contemporary context of Brazilian education and the persecutions imposed on researchers of gender and sexuality in the field of education through conservative sectors of society, especially of Christian origin, in order to delegitimize and disqualify this area of knowledge by coining the term “gender ideology”. In this sense, it also proposes the unraveling of a new conceptual product, a sort of '' genesis ideology '', influenced by the Christian religion and propagated by these very agents, who now use biblical teachings as a form to 'interdict' bodies and safeguard their entrances in “Christ’s Heaven”. Gender Studies and Foucault’s philosophy (2004, 2008, 2014a, 2014b) are the main references. The paper is the result of a theoretical and bibliographic research, sustained by Philosophy. The period analyzed comprises the decade of 2010-2020, marked in the Brazilian political scene by massive instability and the rise of neoconservatism.